(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This study investigates the synthesis of carboxymethylinulin via the suspension method in an isopropyl alcohol medium. The effects of mercerization, temperature, reaction time, and the concentration of the alkylating reagent on the physicochemical properties of the reaction products are examined. The results demonstrate that the degree of substitution of inulin esters, as well as their molecular characteristics, are strongly dependent on reaction conditions. These findings highlight the potential of carboxymethylated inulin as a functional derivative with valuable properties for use in food, pharmaceutical, and chemical industries. These findings could serve as a basis for further research on the industrial applications of carboxymethylated inulin.